Neuropsychological test performance in social anxiety disorder. (August 2015) - O'Toole, Mia Skytte; Pedersen, Anders Degn; Hougaard, Esben; Rosenberg, Nicole K.
Abstract Background: The effect of state factors on neuropsychological performance in social anxiety disorder (SAD) has not been thoroughly investigated and the overall neuropsychological profile remains poorly understood. Aims: The primary objective of the study was to investigate the effect of state anxiety and state emotion suppression on neuropsychological performance in SAD. Methods: A neuropsychological test battery was administered before and after an anxiety manipulation (instruction to give a video-recorded speech) to 42 patients with SAD and to a gender and education matched group of 42 healthy controls (HCs). Results: Overall, participants with SAD performed worse than HCs on processing speed, visuospatial construction, visuospatial memory, verbal learning and word fluency, of which only the decreased visuospatial construction performance was considered clinically significant. State anxiety was not associated with neuropsychological performance at baseline, whereas state emotion suppression predicted decreased visuospatial memory in HCs and decreased verbal learning in the SAD group. Both groups performed better on working memory, processing speed and spatial anticipation, and worse on verbal learning and memory following the anxiety manipulation. The increase in state anxiety was associated with the decrease in verbal learning in both groups. Conclusions: Participants with SAD showed clinically significant difficulties with visuospatial construction and may experience verbal learning difficulties when suppressing emotions and experiencing an increase in anxiety.